PENGARUH HARGA PAKET DAN KUALITAS JARINGAN INTERNET TERHADAP LOYALITAS PELANGGAN TELKOMSEL DI WILAYAH DESA KALIGLAGAH (STIE Rajawali Purworejo, 2021)
The aim of this research is to examine the influence of package prices and network quality on Telkomsel card customer loyalty in the Kaliglagah Village area. The sampling technique in this research uses a non-probability technique, namely the incidential sampling technique. The population of Telkomsel card users is infinite, so the number of samples in this study was calculated using the Lemeshow formula with a result of 100 respondents. The data analysis technique used in this research is the Likert scale, validity and reliability tests. Correlation coefficient test, multiple linear regression test, determination analysis, t test, and F test. The results of the multiple linear regression test calculation, the number Y = 6.105 + 0.411X1 + 0.252X2 shows that every time there is an increase in one score for the package price variable, it increases customer loyalty by 0.411, every time there is an increase in one score for the network quality variable there will be an increase in customer loyalty by 0.252. The determination test obtained a coefficient of determination of 0.559 that the customer loyalty variable can be influenced by the package price and network quality variables by 55.9%. From the t test, it can be concluded that the package price variable (X1) has a positive and significant effect on the customer loyalty variable because it has a significance of 0.000 (P> 0.05) and the tcount > ttable (4.601 > 1.984), meaning the package price variable (X1 ) has a positive and significant effect on customer loyalty (Y). The same applies to the network quality variable (X2) which has a significance of 0.000 (P> 0.05) and a value of tcount > ttable (3.086 > 1.984), so it can be concluded that the network quality variable (X2) has a positive and significant effect on consumer loyalty (Y). . Customer loyalty can be increased by providing additional facilities on the card in the form of affordable Telkomsel card prices, and maintaining stable network quality.